Planning and construction for the NFV of core network - Lei SHEN; Lihua WU (Dianxin kexue)
In September 2015,China Mobile launched a pilot project of NFV network,and applied NFV framework for the construction of“the new call”,“the new message”platform in the converged communications project.NFV is the integration of IT and CT,and combined their characteristics during planning and construction; but due to the fact that this technology is not yet mature,there are some problems gradually exposed in the planning and construction of the current NFV network.Based on the experience of several China Mobile's NFV projects,the key problems in NFV planning and construction were discussed and summarized.